Effectiveness of Reading Remediation Program for Grade One Low Emerging Readers - Concepcion, Roselle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of the Reading Remediation Program for Grade One low emerging readers at Baras Pinugay Elementary School, Baras Sub-Office, Division of Rizal, during the School Year 2025–2026. Specifically, it assessed learners’ reading performance before and after the intervention in terms of phonics, word recognition, and comprehension and examined differences when grouped according to selected demographic variables. Using an experimental research design, the study involved 32 Grade One low emerging readers who underwent pretest and posttest assessments. Findings revealed that the Reading Remediation Program significantly improved learners’ phonics skills and overall reading performance, resulting in higher posttest scores and more learners attaining the Outstanding level. However, improvements in word recognition and comprehension were not statistically significant, indicating that higher-order reading skills require more sustained and targeted instructional support. Most demographic variables, including sex, birth order, family size, parental occupation, mother’s educational attainment, and family income, showed no significant influence on posttest reading performance, whereas father’s educational attainment significantly affected learners’ reading achievement. The study concludes that the Reading Remediation Program is effective in strengthening foundational decoding skills but requires longer implementation and enhanced instructional strategies to improve word recognition and reading comprehension. It is recommended that schools strengthen reading interventions through adequate instructional resources, teacher professional development, targeted comprehension activities, and active parental involvement to further enhance learners’ reading outcomes.